Performing English online: The use of Instagram Reels for developing basic speaking and multimodal awareness - Fitrilya Anjarsari; Estiningtyas Sholikhah (Universitas Islam Malang, 2026)
Growing use of short-form video platforms has transformed how undergraduates encounter English, yet classroom speaking tasks rarely exploit these multimodal, audience-oriented spaces. Previous EFL studies on TikTok and Instagram report higher motivation but give limited accounts of how learners coordinate gesture, on-screen text, and voice, and rarely link this to gains in speaking performance. This study addresses that gap by examining how Instagram Reels-based storytelling tasks support basic speaking development and multimodal awareness in a first-year EFL class. Using a classroom-based mixed-methods design, the research involved 38 undergraduates in a Speaking course. Students completed three Instagram Reels narrative tasks alongside in-class speaking activities. Data comprised speaking tests rated with an analytic rubric, 114 student videos analysed through multimodal discourse analysis, and reflective journals plus interviews. Quantitative results show a moderate increase in speaking scores (mean gain 1.1/5), with the largest improvements in fluency and discourse management. Multimodal analysis indicates a shift from static monologues to more coordinated use of gaze, framing, and captioning aligned with spoken content. Learners reported that opportunities to rehearse, edit, and address an imagined online audience reduced anxiety and encouraged more extended speech. The study is limited by its single-institution context, modest sample, and reliance on researcher-designed rubrics, constraining generalizability. Nevertheless, it offers practical implications for integrating short-form video as a multiliteracies-oriented task in speaking syllabi and highlights the need for guidelines on ethics, privacy, and assessment. Future research could compare alternative platforms, incorporate peer feedback, and track impacts on EFL learners’ identities as English users.